Mathematics with applications for the management, life, and social sciences - Anton, Howard; Kolman, Bernard; Averbach, Bonnie (San Diego : Harcourt Brace Jovanovich, 1988)
This book covers a selected range of topics in the field of finite mathematics. Students majoring in the social and behavioural sciences, biology, finance, and business will find it useful. The nineteen chapters develop the following topics: set theory; coordinate systems and graphs; functions; linear programming (geometric and algebraic approaches); counting techniques, permutations and combinations; probability; statistics; mathematics of finance; and calculus
Includes index.
lje 17/10/2018
Loans
Keywords: Mathematics